2016
DOI: 10.4103/2249-4863.197284
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure (BP) control and perceived family support in patients with essential hypertension seen at a primary care clinic in Western Nigeria

Abstract: Context:Nonadherence to therapeutic plans has been reported among hypertensive patients. Researchers have also shown that adherence to therapeutic plans improves if motivation in the form of social support is provided. There is a dearth of local studies that explore the influence of family support on treatment outcomes of hypertensive patients.Aims:The aim of the study was to determine the relationship between BP control and perceived family support in patients with essential hypertension seen at a primary car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
31
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 30 publications
13
31
0
9
Order By: Relevance
“…Family can directly show empathy, show caring attitude, and monitor the schedule of the activities of the older persons (Prazeres & Santiago, 2015). The higher the support provided by the family for the older persons is, the more motivated the older persons to perform regular and sustainable activities are (Ojo, Malomo, & Sogunle, 2016). This is also consonant with the fi ndings reported by Miller & DiMatteo (2013) which states that there is a positive and signifi cant correlation between family support and adherence where family can be a support system towards the health problems experienced by individuals.…”
Section: Discussionsupporting
confidence: 74%
“…Family can directly show empathy, show caring attitude, and monitor the schedule of the activities of the older persons (Prazeres & Santiago, 2015). The higher the support provided by the family for the older persons is, the more motivated the older persons to perform regular and sustainable activities are (Ojo, Malomo, & Sogunle, 2016). This is also consonant with the fi ndings reported by Miller & DiMatteo (2013) which states that there is a positive and signifi cant correlation between family support and adherence where family can be a support system towards the health problems experienced by individuals.…”
Section: Discussionsupporting
confidence: 74%
“…The scale contains 20 items to be answered by yes, no, or don't know. A score of 1 is assigned to each yes response; the other responses, no and don't know, are each scored as a 0 as in other research studies (Ojo, Malomo, & Sogunle, ; Olowookere et al, ). Total scores can range from 0 (no perceived family social support) to 20 (maximum perceived family social support).…”
Section: Methodsmentioning
confidence: 99%
“…Total scores can range from 0 (no perceived family social support) to 20 (maximum perceived family social support). The scores have previously been categorized to represent strong family support (greater than or equal to 11), weak family support (7‐10), and no family support (less than or equal to 6) (Ojo et al, ). The original family support scale demonstrated acceptable internal consistency (Cronbach α = .90) (Procidano & Heller, ).…”
Section: Methodsmentioning
confidence: 99%
“…Family plays a role in preventing health problems and caring for sick family members as well. Studies found that families, friends and significant others are the supportive people who can directly prevent and improve patient's health (Ojo, Malomo, & Sogunle, 2016;Osamor, 2015;Padhy, Lalnuntluangi, Chelli, & Padiri, 2016). The influence of family involvement in chronic disease control especially hypertension had been proven by many studies.…”
Section: Introductionmentioning
confidence: 99%
“…This is also revealed by Osamor (2015) that says support from family by giving reminders about medication shows better treatment compliance than those who did not. In addition, Ojo et al (2016) states that a strong perceived family support will improve their self-worth and motivation. Based on some observations, most hypertensive patients have good knowledge about hypertension but family does not realize that their support is crucial.…”
Section: Introductionmentioning
confidence: 99%